2008
DOI: 10.1098/rstb.2008.0123
|View full text |Cite
|
Sign up to set email alerts
|

Proton-coupled gating in chloride channels

Abstract: The physiologically indispensable chloride channel (CLC) family is split into two classes of membrane proteins: chloride channels and chloride/proton antiporters. In this article we focus on the relationship between these two groups and specifically review the role of protons in chloride-channel gating. Moreover, we discuss the evidence for proton transport through the chloride channels and explore the possible pathways that the protons could take through the chloride channels. We present results of a mutagene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 43 publications
4
29
0
Order By: Relevance
“…Intriguingly this glutamate residue is not conserved in CmClC antiporters either, suggesting the existence of an alternate H þ transport pathway 13 . Lisal and Maduke 53 have suggested that another highly conserved glutamate residue on helix H, E291 ( Supplementary Fig. S1), may be part of the H þ transport pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly this glutamate residue is not conserved in CmClC antiporters either, suggesting the existence of an alternate H þ transport pathway 13 . Lisal and Maduke 53 have suggested that another highly conserved glutamate residue on helix H, E291 ( Supplementary Fig. S1), may be part of the H þ transport pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the asymmetry of ClC-0 gating is driven by the proton gradient, and not the gradient for Cl − . These authors suggest that this is remnant of evolution of ion channels from an ancestral transporter (64, 66). This idea is strengthened by data that other ClC channels show pH-dependent changes in activity.…”
Section: A Thin Line Between Channels and Transportersmentioning
confidence: 99%
“…It has been proposed that a conserved Glutamate residue next to Glu in , serves as the intracellular H + acceptor in CLC channels [75-76]. When this residue, E291 in CLC-1, is mutated to Aspartate or Glutamine there is a drastic reduction in the open probability of the channel and a loss of sensitivity of the currents to the intracellular H + concentration [76]. While these results do not prove that E291 acts as a Glu in surrogate they are at least consistent with this hypothesis.…”
Section: A Degraded H+ Pathway Exists In the Clc Channelsmentioning
confidence: 99%